Fibrin Gel Induces the Migration of Smooth Muscle Cells from Rabbit Aortic Explants - Nomura, Hideki; Naito, Michitaka; Iguchi, Akihisa; Thompson, W. Douglas; Smith, Elspeth B. (Thrombosis and Haemostasis, 1999)
A major step in the pathogenesis of atherosclerosis is the vectorial migration of smooth muscle cells (SMCs) from the arterial media into the intima. Although subcultured SMCs usually show synthetic phenotype, the behaviour of contractile SMCs may be crucial for the subsequent migration of the cells. In the present study, we utilized an in vitro assay system to evaluate the effects of fibrin gels on the migration of SMCs from explants taken from rabbit aorta. After cultured for 5-7 days in a serum-free condition, SMCs appeared from explants covered with fibrin gel. The cells were positive on immunostaining for SMC specific α-actin. No migration of SMCs from the control explants without fibrin gel was observed. Then the percentage of explants showing cell migration and the number of migrating cells increased with time. The migration of SMCs into fibrin gels was not dependent on the concentration of fibrinogen used for the preparation of fibrin gel in the range of 1.5-3 mg/ml. Variations of thrombin concentration in the range of 0.25-1.25 U/ml had no significant effect. However, there was less migration of SMCs with higher concentrations of thrombin. Thrombin inhibitors, hirudin and PPACK had no significant effect on the migration of SMCs. An RGD-containing peptide, GRGDS inhibited the migration of SMCs although a control peptide GRGES at the same concentration had no significant effect. A monoclonal antibody to αvβ3, LM609, completely inhibited the migration of SMCs from the explants, suggesting that αvβ3 integrin is involved in the migration of SMCs into fibrin gels. SMCs which migrated from the explants showed the positive staining with the monoclonal antibodies against SMC myosin heavy chain isoforms, SMemb, SM1 and SM2, suggesting that they are in an intermediate state changing from contractile to synthetic state. In conclusion, the present study showed that fibrin gel induces the migration of SMCs from explants into itself and the process may not need other growth factors or cytokines.
Keywords: Fibrin gel, smooth muscle cell, migration, phenotype, integrin αvβ3